Relationship between syndrome elements and anterior communicating artery opening in patients with smptomatic severe carotid artery stenosis/occlusion - Zhen Fei; Meng Fanxing; Dou Jinjuan; Louis Lei Jin; Qiu Jiwen (KeAi Communications Co., Ltd., 2021)
Objective: To study the relationship between syndrome elements and anterior communicating artery (ACoA) opening in patients with symptomatic severe carotid artery stenosis/occlusion. Methods: Thirty-six patients with symptomatic severe carotid stenosis/occlusion were collected, including 26 patients with cerebral infarction and 10 patients with transient ischemic attack (TIA). Syndrome elements at five time points were collected. Computer tomography angiography (CTA) combined with magenic resonance angiograp (MRA) was used to evaluate the primary collateral circulation, and the prognosis and syndrome elements were statistically analyzed according to whether the ACoA was open or not. Results: The ACoA was open more in the primary collateral circulation among patients with symptomatic severe carotid stenosis/occlusion. There was a statistically significant difference in national institute of health stroke scale (NIHSS) score improvement and good prognosis [the modified rankin scale (mRS) ≤ 2] between the ACoA open group and the ACoA non-open group on the 90th day (P < 0.05). The proportion of patients with internal wind syndrome, blood stasis syndrome, Qi deficiency syndrome, and Yin deficiency syndrome in the ACoA non-open group was higher than that in the open group. Conclusion: In the patients with severe carotid artery stenosis/ occlusion, the group with presence of anterior communicating artery had better prognosis. The syndrome elements are more complex in the group without the presence of anterior communicating artery. The proportion of Qi deficiency syndrome was positively correlated with the non-opening of anterior communicating artery. The imaging evaluation of collateral circulation can provide guidance for syndrome differentiation and treatment.